Coronavirus Disease 2019 Vaccinations in Patients With Chronic Liver Disease and Liver Transplant Recipients: An Update - Sripongpun, Pimsiri; Pinpathomrat, Nawamin; Bruminhent, Jackrapong; Kaewdech, Apichat (Frontiers in Medicine, 2022)
Coronavirus disease 2019 (COVID-19) is a current global pandemic associated with an increased mortality, particularly in patients with comorbidities. Patients with chronic liver disease (CLD) and liver transplant (LT) recipients are at higher risk of morbidity and mortality after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Many liver societies have recommended these patients should receive COVID-19 vaccinations, although there are limited studies assessing risks and benefits in this population. In addition, two doses of mRNA vaccines may not provide sufficient immune response, and booster dose(s) may be necessary, especially in LT recipients. Notably, variants of concern have recently emerged, and it remains unclear whether currently available vaccines provide adequate and durable protective immunity against these novel variants. This review focuses on the role of COVID-19 vaccinations in CLD and LT recipients.